Robot-assisted internal mammary lymph chain excision for breast cancer: A case report. Issue 35 (September 2017) - Du, Junze; Mo, Hongbiao; Fan, Linjun; Jiang, Jun
Abstract: Rationale: Understanding the status of internal mammary lymph nodes of breast cancer is critical in the accurate staging of breast cancer and the development of accurate therapeutic regimen for selected patients. Current techniques for dissection of internal mammary lymph node biopsy involve endoscopic or Traditional thoracic surgery, An important drawback of the current techniques is the great trauma caused by them. Patient concerns: Da Vinci robotic surgery system (Intuitive Surgical Inc. Sunnyvale, CA) was used to perform the internal mammary lymph chain excision for a breast cancer patient with left internal mammary lymph node metastasis. Diagnoses: Positron emission tomography-computed tomography examination and Ultrasonography examination. Interventions: In this paper, we introduce a Robot-assisted technique for dissection of internal mammary lymph node biopsy with only 3 small trocar ports. This technique reduces the incision size and considerably reduce the trauma. Outcomes: The operation lasted a duration of 1.5 hours. The operation was carried out smoothly with removal of 9 internal mammary lymph nodes in total. The amount of intra operative bleeding was less than 10 ml. The patient's postoperative recovery was fast. 11-month postoperative follow-up showed that the patient recovered well after surgery, no local recurrence or distant metastasis was found, and no obvious discomfort was reported. Lessons: Robot-assisted excision of internal mammary lymph chain in breast cancer is a safe, effective and simple operation with minimal invasion.